Screen time, physical activity, dietary pattern and their interplay among adolescents - Mohnish Tundia; Dhara Thakrar (University of Applied Sciences in Tarnow, Poland, 2023)
Introduction: Adolescence is marked as a critical period of human life because of the rapid physical and sexual growth. Technological advances in recent decades have increased the interaction of adolescents with screen-based technologies. The adolescents have the unhealthiest diets of all age groups, and most adolescents do not meet the national guidelines for physical activity. Objectives: To assess physical activity, dietary pattern and screen time among urban adolescents and to find out association of Screen Time with different variables. Methods: A cross sectional study carried out in Udaipur, Rajasthan with prior permission from ethical committee. The study included 250 adolescents (10 to 19 years) selected by multistage sampling method. The Leisure Time Exercise Questionnaire of Godin and Shephard was used to find out weekly Physical Activity score. Eating habits were investigated using self-administered questionnaire in which we asked different questions about the food consumed by adolescents in a week. A Screen Time of ≥2 hours/ day was categorized as high sedentary behaviour, whereas a Screen Time <2 hours/ day was categorized as low sedentary behavior. Results: In current study prevalence of High Screen Time and unhealthy diet was around 83% and 60% respectively. Around 25% had habit of taking breakfast regularly while less than 30% were taking meal without fail. Screen Time found to be associated significantly with physical activity p < 0.01, gender (p = 0.01) and diet p < 0.01. Conclusion: Screen Time was found to be associated significantly with physical activity, gender and type of diet, whereas it has no role to play with phases of adolescence.